Understanding the Relationship Between Land Use, Land Cover Changes, and Water Quality in Polluted Urban Water Systems: A Remote Sensing Perspective - Muwanwa Phunge; Inos Dhau; Lee-Ann Modley (Air, Soil and Water Research)
Land use and land cover change threaten the ecological state of the most polluted urban catchment in South Africa due to the loss of biodiversity. For a country undergoing rapid economic growth, monitoring the impact of land use on water quality provides effective water management mitigations. Therefore, this study aimed to assess the impact of land use and land cover changes on water quality. Historical land use and land cover and water quality data from 2003, 2008, 2013, 2018, and 2023 were used to determine the correlation. Supervised classification with a maximum likelihood classifier was applied to generate LULC classification maps for the selected periods. The Spearman correlation model was used to determine the relationship between LULC change and water quality variables. The results of the LULC change from 2003 to 2023 revealed an increase in residential areas, bare soil, and mines; meanwhile, forest/agriculture and water bodies recorded a decreasing trend. The study findings highlighted the need to adopt sustainable land use management practices to minimise further water quality deterioration in the Klip River.